Dynamics of Neuromuscular Transmission Reproduced by Calcium-Dependent and Reversible Serial Transitions in the Vesicle Fusion Complex - Martínez-Valencia, Alejandro; Ramírez-Santiago, Guillermo; De-Miguel, Francisco F. (Frontiers in Synaptic Neuroscience, 2022)
Neuromuscular transmission, from spontaneous release to facilitation and depression was accurately reproduced by a mechanistic kinetic model of sequential maturation transitions in the molecular fusion complex. The model incorporates three predictions. First, calcium-dependent forward transitions take vesicles from docked to pre-primed to primed states, followed by fusion. Second, pre-priming and priming are reversible. Third, fusion and recycling are unidirectional. The model was fed with experimental data from previous studies while the backward (β) and recycling () rate constant values were fitted. Classical experiments were successfully reproduced with four transition states in the model when every forward (α) rate constant had the same value, and both backward rate constants were 50-100 times larger. Such disproportion originated an abruptly decreasing gradient of resting vesicles from docked to primed states. By contrast, a three-state version of the model failed to reproduce the dynamics of transmission by using the same set of parameters. Simulations predict that: i. Spontaneous release reflects primed to fusion spontaneous transitions. ii. Calcium elevations synchronize the series of forward transitions that lead to fusion. iii Facilitation reflects a transient increase of priming following the calcium-dependent maturation transitions. iv. The calcium sensors that produce facilitation are those that evoke the transitions form docked to primed states. v. Backward transitions and recycling restore the resting state. vi. Depression reflects backward transitions and slow recycling after intense release. Altogether, our results predict that fusion is produced by one calcium sensor, while the modulation of the number of vesicles that fuse depends on the calcium sensors that promote the early transition states. Such finely-tuned kinetics offers a mechanism for collective non-linear transitional adaptations of a homogeneous vesicle pool to the ever-changing pattern of electrical activity in the neuromuscular junction.